Apego parental y habilidades sociales en estudiantes de la Carrera de Psicología Clínica de la Unach, Riobamba 2020. - Estrada Chávez, Enma Lisseth (2020)
The present investigation had as objective to analyze the parental attachment and the social abilities in students of the career of Clinical Psychology of the UNACH. It was carried out in a population conformed by 105 students of the current mayor, 73 women and 32 men, with age, understood from 18 to 28 years old, a mean of 19 years old, and a standard deviation of 1.42. The methodology had a quantitative approach of bibliographic type of field, with a cross-sectional design, not experimental cut, and a descriptive, correlational level. Digitally, the questionnaires Camir- r was applied to measure social skills. In the stories of attachment and Scale to measure the levels of mastery. The results identified that most of the population presents insecure attachment, standing out the disorganized attachment with 43.8% in men and 37% in women. On the social skills scale, men had a higher percentage of the branch with 25% compared to women who obtained 6.8%, but, when taking into account the general rate of the population, it was evident that the medium level prevailed with 42.9% and the low level with 42.15%. Regarding the correlation between the factors involved, in the two variables, it was found that there are both positive and negative relationships. Therefore, the most striking results are among the elements. A family concern, saying no, and cutting off interactions, with the -,269** in turn self- sufficiency and resentment with initiating positive interactions, with the 733**. These results allowed us to determine the existence of a significant relationship between attachment and social skills.